Aggregate demand policy in mature and dual economies - Peter Skott (University of Massachusetts, Department of Economics, 2019)
Aggregate demand is important, both in the short and the long run, but a basic distinction must be made between dual and mature economies. Mature economies may suffer from a structural aggregate problem ("secu- lar stagnation"): full-employment growth may be impossible in the absence of sustained fiscal stimulus. Dual economies with high levels of open or hidden unemployment, by contrast, do not face long-run structural ag- gregate demand problems. They require public investment in key areas, including education and infrastructure, but the key problems concern the composition of demand and the need to expand the modern sector. These economies face structural transformation problems.
Keywords: 330